Development of ASEAN Food Security Information System of Malaysia (AFSIS-MY) software requirements, testing and user training - Junus, Mazlan (2006)
ASEAN Food Security Information System of Malaysia (AFSIS-MY) Project is implemented to support for data collection process which involves four category of user which are District, State, Head Quarters, and Ministry. The main functionalities that the system should offer are Provide Data, Verify Data and Retrieve Report. In a limited time given, it is difficult to include all categories of users or their representatives which spreading over the country to participate in the requirements gathering, held during the requirements analysis phase. Only generic requirements of the main functionalities could be gathered through the discussion with the Ministry users, while another or additional requirements may come in from others but could not be discussed. However, at the end of the project, the goal to produce AFSIS-MY that satisfied all the users, is achieved. This paper discusses about how the developer strategies the Software Requirements, the Testing, and Training activities in order to produce the quality AFSIS-MY software in terms of conforming and satisfying user’s needs and usability.